Zaangażowanie rodziny Pusłowskich w rozwój przemysłu na Litwie i w Królestwie Polskim w XIX i w początkach XX wieku - Oettingen, Urszula (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2010)
The aim of this article is to show the aristocratic and gentry activity of the Pusłowski family in economic field with special regard to industry. The Pusłowski family came from Lithuania. They achieved great importance owing to Wojciech Pusłowski (1762–1833) who strengthened the financial and social status of the family by managing the economic affairs. With his activity in the first half of the 19th century he laid the foundations for development of agricultural, food, timber, paper, mineral, textile and leather industry on the territory of Lithuania. He founded brickyards, sawmills, cloth factories, papermills, mills, breweries, tar plants, distilleries, tanneries, turpentine factories and he also built roads. He dealt with trade on a large scale. He used to it water communication: the River Niemen and its tributaries. He brought modern machines to his factories. In production he used the natural resources of Lithuania, especially the abundance of forests. The most well-known centres included paper factory in Kuczkuryszki, cloth factory in Chomsk and the factory with its settlement in Albertynin in the vicinity of Słonim, which produced cloth, carpets, linen and hardware. One of his five sons, Władysław (1801–1859), followed in his father’s footsteps. He inherited the most important factories and a gift for managing the economic affairs. In the enclosed Annex II there were presented fragments of letters from 1859 which were addressed to him. In them his plenipotentiaries informed him exactly of economic and financial affairs of his property. Carrying on their industrial activity in Lithuania, in the middle of the 19th century the Pusłowski family bought lands on the territory of the Kingdom of Poland in Warsaw and Czarkowy on the River Nida. In Czarkowy at the beginning of the 1870s they built a modern plant to smelt sulphur from the ore that was found in the area. At the beginning of the 20th century the Pusłowski family also owned ironworks in Chlewiska. Economic activity of the family was marked most of all in Lithuania. Not without reason Wojciech Pusłowski was recognized as the pioneer of its industrialization.